Tandem Promoters for Expression of Cnu, a Nucleoid Protein, in Escherichia coli. (17th June 2019) - Lee, Seol‐Hoon; Kim, Wonkyong; Choi, Jee Soo; Jang, Seonghui; Lim, Heon Man; Lee, Younghoon
Abstract : P1, P2, and P3, three tandem promoters of cnu .